An experimental study of computer-based negotiation in property development processes - Samsura, Datuk Ary Adriansyah; Deemen, Adrian van; Krabben, Erwin van der; Heijden, Rob van der (International Journal of Strategic Property Management, 2014)
This paper reports an experiment based on the model of bilateral sequential bargaining over the distribution of a certain value in a laboratory setting within a real specific context of property development in the Netherlands. We have involved only property development professionals as participants in the experiment who have experience with the context. We have also extended the experiment into three different negotiation games distinguished by the availability of information to the participants: a negotiation game with incomplete information, asymmetric information, and complete information. We have found in this experiment that the availability of information could affect the plausibility to reach an agreement, particularly due to a restricted communication setting. This study also provides evidences that it is in the negotiators’ concern to reach an agreement with a fair outcome, which is defined here as the equilibrium, regardless the availability of the information to them. First Publish Online: 8 Dec 2014